Пространственная структура поселения Marmota bobak на северо-востоке Украины - Савченко, Г.А.; Ронкин, В.И.; Savchenko, G.A.; Ronkin, V.I. (Харьковский национальный университет имени В.Н.Каразина (Харьков, Украина), 2008)
В 1992–2007 гг. изучали пространственную структуру поселения степных сурков (Müller, 1776) на стационарном участке исследований (с. Нестеривка, Великобурлукский р-н, Харьковская обл.). Приводится общее число и плотность нор, доля нор разных категорий, их соотношение и распределение по территории. На основании плотности постоянных нор и плотности населения степных сурков выделены две части поселения: экологический центр и экологическая периферия. Приводятся количественные характеристики семейных участков степного сурка в разных по степени хозяйственного использования типах местообитаний. Обсуждается влияние на пространственную структуру поселения фактора рельефа и средообразующего воздействия крупных домашних копытных. Рассматривается роль градиента средообразующих эффектов для стабильного существования поселений степного сурка.
Spatial structure of Marmota bobak settlement in North-Eastern Ukraine
The spatial structure of steppe marmot settlement was studied in 1992–2007 at a stationary site in North-Eastern Ukraine (village Nesterivka, Velikoburluk district, Kharkov region). General number and density of burrows, the ratio of different categories of burrows, their proportion and distribution on the territory are presented. On the basis of the constant burrows density and the density of marmot population two parts of the settlement are established: ecological center and ecological periphery. The quantitative characteristics of home-ranges of marmot family groups in habitats which differ by degree of grazing pressure are presented. The influence of the orographical factor and environment-formed effect of cattle grazing on the spatial structure of marmot settlement is discussed. The role of a gradient presence of both effects for stable existence of steppe marmot population is considered.
Keywords: степной сурок; структура поселения; экологический центр поселения; экологическая периферия поселения; steppe marmot; spatial structure of; ecological center; ecological periphery